Program to improve fruit availability in a workplace and its effect on the perception of consumption by employees (2017)
ABSTRACT: Background and objectives: Grupo Éxito, is the biggest private employer in Colombia, with an amount of 42.000 employees, contemplates in its Nutrition Policy the promotion of a healthy work place, which aims contribute to the integral health of its employees through programs of health promotion and disease prevention. One of the actions implemented within this strategy is the program that delivery fruit in the office, began in 2015. The aim of this paper was analyze a change perception in the consumption of fruits in the employees who were impact by the program in its first year. Methods: Cross-sectional study. A total 2,399 employees were qualified to answer the survey during two weeks on the company’s virtual platform. The survey includes next variables: daily fruit consumption, portions of fruit consumed per day, origin of the fruit consumed, change perception of the amount of fruit consumed since the beginning of the program. A descriptive analysis was performed using X2 tests to establish the relationship between the variables of interest. α = 0.05. SPSS software v.23. Results: 282 employees answered the survey, 11.8% of the qualified employees. 78.7% reported consuming fruit daily, of these 30.9% consume one serving daily, 33.0% two portions, 17.7% three portions and 17.0% four or more servings per day. The consumption of fruit comes mostly from the program offered by the company, followed by the home and finally from other sources such as retail. About the increase in fruit consumption, 64% of surveyed mentioned that their consumption increased with the program. A significant relationship was found between the increase of fruit consumption and the implementation of the program (p = 0.0087).Conclusions: The companies can implement small actions such as facilitating access and availability of fruits in the workplace, promoting an adequate diet and providing environmental support for the achievement of healthy eating habits. Conflict of Interest Disclosure: This research project is funded by Grupo Éxito. The opinions expressed are those of the authors and do not necessarily represent the views or recommendations of their Affiliations.